Formulation and Evaluation of Hydrogel Incorporated with Biophytum sensitivum Extract - Ranit Bandyopadhyay; Ashly Merin George; Selvakumar K; Pratiti Sanyal; Pabitra Samanta; Madhu Kumari; Sourav Nath (RGUHS Journal of Pharmaceutical Sciences, 2025)
Background Biophytum sensitivum Linn. represents a promising natural source for the development of hydrogels with potential biomedical applications leveraging its rich medicinal properties for therapeutic benefits in wound healing dermatology and beyond.AimsObjectives In this study Biophytum sensitivum Linn. extract was incorporated into the hydrogel formulation.Methods The formulated hydrogels were evaluated for the appearance homogeneity texture spreadability pH viscosity and extrudability.Results The optimised formulation demonstrated good antimicrobial activity compared to the standard Azithromycin solution. Stability studies conducted at 40plusmn2 RH 75plusmn5 for two months showed no significant degradation of product.Conclusion These findings support the formulation of Biophytum sensitivum Linn. incorporated hydrogel highlighting its strong potential as an antibacterial agent. When delivered in hydrogel form it may offer enhanced therapeutic benefits for the treatment of common skin conditions infections wounds ulcers injuries and diabetes related complications.